Defining new dung beetle tribes to resolve discrepancies between phylogeny and tribal classification in the subfamily Scarabaeinae (Coleoptera: Scarabaeidae) - Davis, Adrian L.v.; Deschodt, Christian M.; Scholtz, Clarke H. (Zootaxa, 2019)
The monophyletic, dung beetle subfamily, Scarabaeinae, has a long history of subdivision into tribes and subtribes represented by groups of genera unified by designated characters. Various tribal names have been proposed although only 11 or 12 were considered valid in recent reviews. Three of these 12 tribes have now been invalidated due to extensive polyphyly indicated by both morphological and molecular phylogenies. Although partial revision of tribal classification was proposed in the most recent global molecular phylogeny of the subfamily, this was primarily limited to redefinition of membership or provision of support for pre-existing tribes. Complete revision was not attempted as the phylogeny examined interrelationships between only 52% of the valid described genera. It was also hampered by inconsistencies in topology using different analytical methods, weakened by limited bootstrap support for many basal nodes, as well predicting several phylogenetic relationships that seemed anomalous with regards to biogeographical hypotheses. Nevertheless, using this phylogeny, we propose further revision of tribal classification in a clade of primarily African genera included within a group defined as “basal Scarabaeinae”. Using three different methods, the sister lineages of this clade were consistently recovered, mostly with strong bootstrap support for their molecular relatedness. Therefore, we provide a number of defining morphological characters to support their proposed designation as three new tribes: Byrrhidiini, Endroedyolini and Odontolomini. We also discuss approaches to a full tribal revision as well as the implications for historical biogeography of the Scarabaeinae.